Low photoactive phase temperature all-inorganic, tin–lead mixed perovskite solar cell. Issue 6 (15th January 2021) - Kuan, Chun-Hsiao; Shen, Hui-Hung; Lin, Ching-Fuh
Abstract : In Cs-based all inorganic perovskite solar cells based, doping Sn can cause lattice shrinkage, which reduces annealing temperature of forming photoactive phase. Abstract : CsPbI3 films have recently attracted significant attention as efficient absorbers for thermally stable photovoltaic devices. However, their large bandgap and photoactive black phase formation at high temperature impede their use for practical applications. Using the concept of lattice contraction, we demonstrate a low bandgap (≤1.44 eV) cesium-based inorganic perovskite CsPb x Sn1− x I3 that can be solution processed at low temperature for photovoltaic devices. The results from systematic measurements imply that the partial substitution of lead (Pb) with tin (Sn) results in crystal lattice contraction, which is essential for realizing photoactive phase formation at l00 °C and stabilizing photoactive phase at room temperature. These findings demonstrate the potential of using cesium-based inorganic perovskite as viable alternatives to MA- or FA-based perovskite photovoltaic materials.